EP154/#912 Compliance of surgical care in patients with carcinoma endometrium in a tertiary care centre, to European society of gynaecologic oncology (ESGO) quality indicators. (4th December 2022) - Thiagarajan, Monica; Thomas, Anitha; Thomas, Vinotha; Sebastian, Ajit; Thomas, Dhanya; George, Rachel; Milton, Sharon; Daniel, Sherin; John, Neenu; Thumaty, Divya; Chandramohan, Anuradha; Ram, Thomas
Abstract : Objectives: Endometrial cancer treated surgically followed by tailored adjuvant treatment has shown to have very good prognosis. The quality of surgical care should be optimal for attaining the maximum survival benefit. To standardize surgical management, ESGO has put forth quality indicators. To audit the surgical care provided at our centre we wanted to assess the compliance to these indicators and find areas of improvement. Methods: This is a retrospective audit done in the Department of Gynaecologic Oncology. Electronic medical records of patients who underwent surgical management of carcinoma endometrium from Jan2020-Dec2021 were assessed. Results: A total of 163 patients had undergone primary surgery and 2 patients for recurrence. The audit showed that the target for categories of general indicators and pre-operative work-up were met. There was lack in compliance of the intraoperative management, with only 34% among presumed early-stage disease undergoing successful MIS, 31% undergoing sentinel lymph node procedure and 53% among them being done using indocyanine green with 18% bilateral mapping rate. None of the patients had complete molecular classification. Compliance of adjuvant treatment provided was adequate. Minimal required elements in surgical reports were in 81% and pathological reports in 91% of patients falling short of the set target. Conclusions: The audit helped us identify the need to increase MIS, use and adapt sentinel lymph node procedure with ICG dye more aggressively. There also is a need for improvement in documentation of pertinent information on surgical and pathology reporting. Molecular classification should be routinely incorporated into the diagnostic algorithm to aid in adjuvant therapy.